Refleksi Ekonomi Syariah Dalam Melihat Krisis Moneter Di Indonesia - Devina Sulistyawati; Siti Sokhiful Jannah; Solahuddin Al-Ayubi (Tathawwur: Jurnal Ekonomi Pembangunan dan Keuangan Islam, 2024)
This study aims to provide a view of Sharia Economics in looking at the monetary crisis in Indonesia. This research uses literature study methods from various sources such as books, journals, notes, and reports to understand the meaning, context, and complexity of the problems faced. The results indicate that the monetary crisis occurred due to unequal distribution of income and wealth, usury in the economic system, and the absence of a filter mechanism that was socially agreed upon in the economic system. Islam as a kaffah religion certainly has solutions and economic systems that are considered capable of providing a new atmosphere for the world economy. Where Islam offers a system that prioritizes transparency, honesty, and moral responsibility based on Sharia and religious law. Through Islamic economics, Islam offers four strategies. It includes a reorganization of the entire economic system with 4 mutually reinforcing elements: first, a socially agreed filter mechanism, second, a motivational system that encourages individuals to do what is best for themselves and their society, third, restructuring the economy as a whole with the aim of realizing maqasid despite the scarcity of resources; and fourth, a positive and strong role of government.